Prophylactic Ephedrine versus Phenylephrine Administration on Hemodynamic Parameters in Surgical Patients in the Prone Position: A Prospective Randomized Study - Reza Irawan (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: The changes in position of the patient from supine to prone during general anesthesia often led to hemodynamic disturbances, especially hypotension due to decreased venous return and vasodilation induced by anesthetics. Intraoperative hypotension can jeopardize perfusion of vital organs, and preventive strategies are warranted. Prophylactically, vasopressors like ephedrine and phenylephrine are administered to maintain hemodynamic stability; however, their mechanisms of action and clinical effects vary. Objective: This study aims to compare the effectiveness of prophylactic ephedrine and phenylephrine on hemodynamic stability for surgical patients in the prone position at Dr. Zainoel Abidin Regional General Hospital, Banda Aceh. Methods: This is a prospective randomized study of 38 patients who were divided into two groups receiving ephedrine or phenylephrine. The hemodynamic parameters assessed were the systolic blood pressure, diastolic blood pressure, MAP, and heart rate. Measurements were made prior to induction of anesthesia and at 5 and 10 minutes after patients were positioned in the prone position. Results: There was no statistically significant difference in systolic and diastolic blood pressure between the two groups. Patients who received ephedrine showed a higher and more prolonged rise in MAP. Furthermore, ephedrine induced a significantly greater heart rate at 10 minutes versus phenylephrine. Conclusion: In conclusion, ephedrine produced higher and longer-lasting MAP and HR increases via β-adrenergic stimulation; phenylephrine showed shorter, moderate hemodynamic effects with stable HR via α₁-mediated vasoconstriction.